Effect of silver and zinc oxide nanoparticles on the tensile strength of a denture tissue conditioner - Alireza Pournasrollah; Maryam Aghajanzadeh; Seyed Amin Mousavi; AmirHossein Rafiei; Fatemeh Bakhtiari (Journal of Dental Materials and Techniques, 2023)
Objective: Low tensile strength is one of the problems of tissue conditioning materials used in complete prostheses. This study aimed to explore the impact of silver (Ag) and zinc oxide (ZnO) nanoparticles (NPs) on the tensile strength of a tissue conditioner.Methods: Ag and ZnO NPs were synthesized using the light bulb method and verified by scanning electron microscopy, X-ray powder diffraction, and Fourier transform infrared spectroscopy (FTIR). The prepared NPs were mixed with the tissue-conditioner fluid at weight percentages (wt%) of 0.675, 1.25, 2.5, 5, and 10. The NPs were added either individually (Ag or Zn alone) or in combination (at a ratio of ½ Ag and 1/2  ZnO). Tensile strength was measured on rectangular cube specimens with dimensions of 2 x 20 x 200 mm using a universal testing machine according to the ISO 17025 standard. The results were analyzed by one-way analysis of variance (ANOVA) and Tukey test at a significance level of P<0.05. Results: The concentration of 5% and 10% Ag NPs increased the tensile strength of the tissue conditioner (P<0.05), but the addition of ZnO NPs at any concentration (up to wt. of 10%) did not (P>0.05). The combined application of Ag and ZnO NPs at concentrations of 5% and 10% was also effective in enhancing the tensile strength (P<0.05).Conclusions: The addition of Ag or Ag-ZnO NPs at concentrations of 5% and 10% may be suggested to enhance the tensile strength of the tissue conditioning materials. (J Dent Mater Tech 2023;12(2):55-60)